ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) : PENGARUH QUALITY OF WORK LIFE DAN SELF-EFFICACY (Studi Pada Karyawan PT Suzuki Sejahtera Sunindo Trada Kota Semarang) - Ferdina Widiyanti; Alimudin Rizal (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study was shown to see the effect of Quality of Work Life and Self-Efficacy on Organizational Citizenship Behavior on the performance of employees of PT Suzuki Sejahtera Sunindo Trada Semarang. Has as many as 70 workers. The technique of taking samples in this study is using sensus Sampling or taking saturated samples. Take primary data using a questionnaire merhod or data analysis using multiple linear regression. Obtained research that Qualiyy of Work Life is significantly affected by Organizational Citizenship Behavior by 0,407and Self-Efficacy is not affected by Organizational Citizenship Behavior at 0,210 and the significant level is 0,057 > 0,05.